A staff development program for public librarians in the National Capital Region, Philippines - Berdin, Glen P.; Santos, Herminia H.; Cruz, Prudenciana C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
The primary objective of public libraries is to provide service to people from all walks of life. This study investigated the status of public librarians in the National Capital Region with the following objectives: (1) to identify the status of public librarians in terms of goals, capabilities, performance, and position; (2) to analyze the similarities and differences of the respondents' goals, capabilities, performance, and the position they are currently occupying; and (3) to formulate a needs based staff development program for public librarians in response to perceived needs. The descriptive method of research was used, employing a structured questionnaire as primary instrument. The questionnaire was formulated to draw the desired information, supplemented by personal interviews of respondents, regardless if they have passed or not the licensure examination as provided for by R.A. 6966. A universal sample included librarians occupying the positions of Librarian I, II, III, IV, and V.
The following statistical tools were used to analyze and interpret the data: percentage Computation for each question which determineddd the percentage equivalent of the number of respondents who answered yes or no to a particular question; Ranking Method which translated the specific order regarding the priorities and interests of public librarians in accordance with the library's mission arranged in descending order; Separman Rho using the SPSSx (Software Package for Social Science) Batch System which weighed the significant relationship of variables and measurement of association between paired variables, namely: position and performance; performance and length of service; education and performance; licensure examination and performance rating.
Of the 17 public libraries in the National Capital Region, 46 respondents ranging from the position of Librarians I to V qualified as subjects of the study. Of this number, 34 (74 percent) are within the bracket of Librarian I and II. It was found that the gap in educational preparation between library science and non-library science graduates is a slim 6 percent, in spite of the fact that 13 percent of the population are undergraduates. The study also revealed that the greater part of the population, 36(78 percent) have worked for decades in the library, and 24 (52 percent) have been performing their job very well over the years. A total of 14 (30 percent) are licensed while the rest are not. The respondents expressed their interest regarding topics that they think should be included in a staff development program. It was also found that among the variables tested, only B (position) and F (performance) have a significant correlation at .288 level. This means that there is a slight correlation, definite but small relationship. Variable E (licensure examination) and G(perormance rating) have a significant correlation at .180 level, meaning there is a slight, almost negligible correlation. The proposed needs-based staff development would divide the participants into two groups to separate personnel more inclined to learn vital library functions from those who are inclined to learn management functions. Pre-training questionnaires should also be distributed for evaluation purposes and as basis for improved conduct of future training.
Computer print out.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Public librarians -- Philippines -- Manila Metropolitan Area; Library personnel management -- Philippines -- Manila Metropolitan Area